2019
DOI: 10.1007/s00213-019-05246-8
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol (CBD) content in vaporized cannabis does not prevent tetrahydrocannabinol (THC)-induced impairment of driving and cognition

Abstract: Background The main psychoactive component of cannabis, delta-9-tetrahydrocannabinol (THC), can impair driving performance. Cannabidiol (CBD), a non-intoxicating cannabis component, is thought to mitigate certain adverse effects of THC. It is possible then that cannabis containing equivalent CBD and THC will differentially affect driving and cognition relative to THC-dominant cannabis. Aims The present study investigated and compared the effects of THC-dominant and THC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
146
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(186 citation statements)
references
References 56 publications
18
146
3
1
Order By: Relevance
“…The current study therefore sought to evaluate the performance of the DW5s and DT5000 POCT devices relative to liquid chromatography−tandem mass spectrometry (LC–MS/MS) confirmatory analysis following controlled laboratory vaporization of THC‐dominant (11% THC, <1% CBD [hereafter ‘THC']); THC/CBD equivalent (11% THC, 11% CBD [hereafter ‘THC/CBD']) and placebo (<1% THC; <1% CBD) cannabis using a double‐blind, within‐subjects, crossover design. This occurred as part of larger study examining the effects of THC‐dominant and THC/CBD‐equivalent cannabis on driving and cognition that has been published elsewhere …”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current study therefore sought to evaluate the performance of the DW5s and DT5000 POCT devices relative to liquid chromatography−tandem mass spectrometry (LC–MS/MS) confirmatory analysis following controlled laboratory vaporization of THC‐dominant (11% THC, <1% CBD [hereafter ‘THC']); THC/CBD equivalent (11% THC, 11% CBD [hereafter ‘THC/CBD']) and placebo (<1% THC; <1% CBD) cannabis using a double‐blind, within‐subjects, crossover design. This occurred as part of larger study examining the effects of THC‐dominant and THC/CBD‐equivalent cannabis on driving and cognition that has been published elsewhere …”
Section: Introductionsupporting
confidence: 90%
“…We recently demonstrated impaired driving performance and reduced confidence in driving ability in these same 14 participants at both 30 and 210 minutes following vaporization. 32 However, at 180 minutes, there were no true positive test results in the present study and THC concentrations were typically below the LOQ. Consistent with this, a controlled laboratory study by Ramaekers et al 42 found only a weak relationship between oral fluid THC concentrations and magnitude of impairment on a range of driving-related cognitive tasks following smoked cannabis.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The peak plasma concentrations were also similar to those reported for day old piglets after 1.0 mg/kg CBD, i.v. (Barata et al, 2019) but higher than those reported in humans (~62 ng/mL) using a plant material vaporizer with 11%THC/11%CBD cannabis (Arkell et al, 2019).…”
Section: Discussionmentioning
confidence: 59%